Noninvasive Diagnosis of PLA2R-Associated Membranous Nephropathy: A Validation Study. Issue 12 (December 2021) - Bobart, Shane A.; Han, Heedeok; Tehranian, Shahrzad; De Vriese, An S.; Roman, Juan Carlos Leon; Sethi, Sanjeev; Zand, Ladan; Andrades Gomez, Cristina; Giesen, Callen D.; Soler, Maria Jose; Bomback, Andrew S.; Fervenza, Fernando C.
Visual Abstract: Abstract : Background and objectives: Kidney biopsy is the current gold standard to diagnose membranous nephropathy. Approximately 70%–80% of patients with primary membranous nephropathy have circulating anti-phospholipase A2 receptor antibodies. We previously demonstrated that in proteinuric patients with preserved eGFR and absence of associated conditions ( e.g., autoimmunity, malignancy, infection, drugs, and paraproteinemia), a positive anti-phospholipase A2 receptor antibody test by ELISA and immunofluorescence assay confirms the diagnosis of membranous nephropathy noninvasively. These data have not been externally validated. Design, setting, participants, & measurements: The clinical and pathologic characteristics of patients with a positive anti-phospholipase A2 receptor antibody test at the Mayo Clinic, the University Hospital Vall D'Hebron (Barcelona), and the Columbia University Medical Center (New York) were retrospectively reviewed. Biopsy findings and presence or absence of a potential associated condition were assessed. Results: From a total of 276 patients with positive anti-phospholipase A2 receptor serology, previously reported patients ( n =33), kidney transplant recipients ( n =9), pediatric patients ( n =2), and patients without kidney biopsy ( n =69) were excluded. Among the 163 remaining patients, associated conditions were identified in 47 patients, and 15 patients had diabetes mellitus. All 101 patients of the final cohort had a primary diagnosis of membranous nephropathy on kidney biopsy. In the 79 patients with eGFR≥60 ml/min per 1.73 m 2, none of the biopsy findings altered diagnosis or management. Among the 22 patients with decreased eGFR, additional findings included superimposed acute interstitial nephritis ( n =1). Conclusions: In patients with preserved eGFR and absence of associated conditions or diabetes, a positive anti-phospholipase A2 receptor test by either ELISA >20 RU/ml or a positive immunofluorescence assay confirms the diagnosis of membranous nephropathy, precluding the requirement for a kidney biopsy.